Classroom Teachers' Strategies in Overcoming Reading Learning Difficulties for Grade II Elementary School Students - Devi Intan Sari Sagala; Tri Indah Kusumawati (Dinasti Publisher, 2024)
An in-depth analysis of the reading challenges encountered by kids in second grade, the factors that amplify these challenges, and the strategies used by second grade teachers to address these concerns are the primary goals of this research. A qualitative research technique is used in this study. The method used is qualitative descriptive analysis. The research included both the students and teachers of Class II. Methods of data collection for this research include recording, observing, and interviewing participants. Based on the findings of this research, second graders often struggle with reading because they either do not know the letters yet, have trouble stringing them into words, leave out letters when reading, stutter when reading, or pronounce them backwards. replace